Hello,
i would go for A)
take it as a guess
Answer:
y=4x
Step-by-step explanation:
it's enough to use first column (x=6, y=24). Inserting this data into equation y=kx, we can calculate k.
24=k*6
6k = 24
k = 24/6
k = 4
Answer:
Step-by-step explanation:
4 “3” Cards in a Deck
52/2=26 Red Cards in a Deck
2/4 “3” Cards in a Deck are red so it would be 26-2=24 I think
Answer: D) 10
============================================================
Explanation:
I'm assuming points M and N are midpoints of segments FD and FE respectively. If that's the case, then segment DE is twice as long compared to segment MN. We consider MN to be a midsegment.
So,
DE = 2*(MN)
3x-2 = 2*(x+4)
3x-2 = 2x+8
3x-2x = 8+2
x = 10
Answer:
<em>T</em><em>h</em><em>e</em><em>v</em><em>a</em><em>l</em><em>u</em><em>e</em><em> </em><em>o</em><em>f</em><em> </em><em>x</em><em>-</em><em>i</em><em>n</em><em>t</em><em>e</em><em>r</em><em>c</em><em>e</em><em>p</em><em>t</em><em> </em><em>i</em><em>s</em><em> </em><em>0</em>
<em>a</em><em>n</em><em>d</em><em> </em><em>y</em><em> </em><em>i</em><em>n</em><em>t</em><em>e</em><em>r</em><em>c</em><em>e</em><em>p</em><em>t</em><em> </em><em>i</em><em>s</em><em>-</em><em>6</em><em>.</em>
Step-by-step explanation:
here,9x+6y=-36
9x = -36 - 6y
x=(-36 -6y)/9
x=(-12-2y)/9.........(i)
putting value of x in question
9[(-12-2y)/9]+6y=-36
-12-2y+6y= -36
-12+4y= -36
4y=-24
y=<em>-</em><em>6</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em>p</em><em>u</em><em>t</em><em>i</em><em>n</em><em>g</em><em> </em><em>v</em><em>a</em><em>l</em><em>u</em><em>e</em><em> </em><em>o</em><em>f</em><em> </em><em>x</em><em> </em><em>i</em><em>n</em><em> </em><em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>i</em><em>)</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>x</em><em>=</em><em>(</em><em>-</em><em>1</em><em>2</em><em>-</em><em>2</em><em>y</em><em>)</em><em>/</em><em>9</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>x</em><em>=</em><em>(</em><em>-</em><em>1</em><em>2</em><em>-</em><em>2</em><em>×</em><em>-</em><em>6</em><em>)</em><em>/</em><em>9</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>x</em><em>=</em><em>0</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em>I</em><em> </em><em>h</em><em>a</em><em>v</em><em>e</em><em> </em><em>d</em><em>o</em><em>n</em><em>e</em><em> </em><em>y</em><em>o</em><em>u</em><em>r</em><em> </em><em>t</em><em>a</em><em>s</em><em>k</em><em>.</em><em> </em><em>B</em><em>u</em><em>t</em><em> </em><em>i</em><em> </em><em>t</em><em>h</em><em>i</em><em>n</em><em>k</em><em> </em><em>i</em><em>t</em><em> </em><em>w</em><em>i</em><em>l</em><em>l</em><em> </em><em>h</em><em>e</em><em>l</em><em>p</em><em> </em><em>y</em><em>o</em><em>u</em><em>.</em><em> </em><em>i</em><em>f</em><em> </em><em>i</em><em>t</em><em> </em><em>h</em><em>e</em><em>l</em><em>p</em><em>s</em><em> </em><em>p</em><em>l</em><em>e</em><em>a</em><em>s</em><em>e</em><em> </em><em>m</em><em>y</em><em> </em><em>a</em><em>n</em><em>s</em><em>w</em><em>e</em><em>r</em><em> </em><em>a</em><em>s</em><em> </em><em>b</em><em>r</em><em>a</em><em>i</em><em>n</em><em>l</em><em>i</em><em>e</em><em>s</em><em>t</em><em> </em><em>a</em><em>n</em><em>s</em><em>w</em><em>e</em><em>r</em><em>.</em><em> </em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>p</em><em>l</em><em>e</em><em>a</em><em>s</em><em>e</em><em> </em><em>d</em><em>o</em><em> </em><em>.</em><em>.</em><em>.</em><em>.</em><em> </em><em>f</em><em>o</em><em>r</em><em> </em><em>m</em><em>y</em><em> </em><em>h</em><em>a</em><em>r</em><em>d</em><em> </em><em>w</em><em>o</em><em>r</em><em>k</em><em>.</em>